A modified insulation material for shielding cables and a method for producing the same
Patent Information
- Application Number
- CN202611403073.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-30
AI Technical Summary
尽管现有技术采用硅烷偶联剂对钛酸钡进行表面处理以改善分散性,但单一的刚性硅烷层无法提供应力缓冲,未能消除界面孔洞的风险
[0032]与现有技术相比,本申请的有益效果至少在于:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of insulating materials, specifically to a modified insulating material for shielded cables and a method for preparing the same. Background Technology
[0002] Shielded cables are widely used in high-voltage power transmission, rail transportation, automotive power systems, engine sensors, and new energy vehicles—environments with strong electromagnetic interference—to effectively suppress electromagnetic leakage and external interference, ensuring reliable transmission of power and signals. The performance of their insulation layer directly determines the electrical safety and service life of the cable and harness. With the increasing challenges of high-density wiring in vehicles and complex electromagnetic / high / low temperature environments, high-energy electron injection can easily induce partial discharge, placing increasingly higher demands on the breakdown strength, resistance to electrical treeing aging, and long-term thermal stability of insulation materials.
[0003] Currently, polypropylene (PP)-based insulation materials are considered an ideal alternative to traditional cross-linked polyethylene (XLPE) due to their excellent electrical insulation properties, thermoplasticity, and recyclability. To improve the toughness of PP and control its dielectric properties, various modification schemes have been proposed in existing technologies. For example, PP can be toughened by adding polyolefin elastomers (POE) to overcome its low-temperature brittleness; or fillers with high dielectric constants can be introduced to uniformly distribute the electric field within the cable insulation layer and suppress partial discharge. Furthermore, adding voltage stabilizers to the matrix is also an effective method to suppress electrical treeing aging of the insulation material under high-voltage electric fields.
[0004] However, the aforementioned existing technologies still face the following technical bottlenecks when applied to high-voltage shielded cables: First, the interfacial compatibility between the filler and the matrix remains unresolved. Barium titanate, as a rigid inorganic filler, exhibits a natural "rigid-flexible" contradiction and modulus abrupt change with the polypropylene organic matrix. During the cooling and solidification process after cable melt extrusion, the crystallization shrinkage of the matrix can induce severe local stress concentration at the filler interface, even tearing out nanoscale micropores. These pores easily accumulate space charge under high-voltage electric fields, becoming sources of partial discharge. Although existing technologies use silane coupling agents to treat the surface of barium titanate to improve dispersibility, a single rigid silane layer cannot provide stress buffering and fails to eliminate the risk of interfacial pores. Second, the long-term stability of voltage stabilizers is insufficient. While conventional voltage stabilizers can capture high-energy electrons, they are mostly small-molecule organic compounds with poor compatibility with the non-polar polypropylene matrix. During long-term high-temperature operation of cables, these stabilizers are prone to thermal migration and surface "sweating" precipitation, leading to rapid decay of their anti-tree function and shortening insulation life. Although existing technologies attempt to graft stabilizers onto the polymer backbone, the process is complex and costly.
[0005] Therefore, how to simultaneously solve multiple problems such as filler dispersion, stress buffering, and long-term anchoring of voltage stabilizers, so that insulating materials have both high breakdown strength and long-term resistance to electrical treeing aging, has become a technical challenge that urgently needs to be overcome in this field. Summary of the Invention
[0006] This application provides a modified insulation material for shielded cables and a method for preparing the same, which aims to improve the breakdown strength and long-term resistance to electrical treeing of the insulation material by introducing modified barium titanate micro powder and aromatic voltage stabilizers.
[0007] In a first aspect, a modified insulation material for shielded cables comprises the following raw materials in parts by weight: 100 parts by weight of isotactic polypropylene matrix, 15-20 parts by weight of polyolefin elastomer, 2-5 parts by weight of modified barium titanate micro powder, 0.5-1 parts by weight of aromatic voltage stabilizer, 0.2-1 parts by weight of perfluoropolyether, and 0.3-0.5 parts by weight of antioxidant. The modified barium titanate micro powder is obtained by treating barium titanate with a phenylsilane coupling agent and a terminal hydroxyl polyether.
[0008] According to this application, by introducing phenylsilane coupling agent and hydroxyl-terminated polyether modified barium titanate micro powder, a coating can be formed on the filler surface, which can alleviate the thermal shrinkage stress concentration between the filler and the matrix during the cooling and curing process. At the same time, it can improve the dispersion uniformity of voltage stabilizer in composite material. In addition, perfluoropolyether can be distributed at the interface by taking advantage of its low surface energy characteristics, which can improve the high voltage DC breakdown resistance and long-term anti-electric treeing properties of modified insulation material.
[0009] Specifically, barium titanate is a rigid inorganic crystal with a significant modulus difference from the polypropylene matrix. During cable extrusion, curing, and shrinkage, it easily tears microscopic pores at the interface, leading to partial discharge. In this application, the barium titanate surface is treated with a phenylsilane coupling agent and a hydroxyl-terminated polyether. The hydroxyl-terminated polyether possesses excellent molecular chain flexibility and high chain segment mobility in its high-temperature molten state. Due to the thermodynamic repulsion of the non-polar polypropylene matrix towards the polar hydroxyl-terminated polyether, the stability of the polyether segments on the surface of the polar barium titanate particles is increased, reducing their detachment or free precipitation into the matrix under strong melt shear. After cooling, it provides an interfacial mechanical buffer between the rigid barium titanate and the flexible polypropylene matrix, alleviating local stress concentration during matrix crystallization and shrinkage, and constructing a smooth rigid-flexible transition phase with high insulation performance.
[0010] Meanwhile, voltage stabilizer molecules have poor compatibility in the non-polar polypropylene matrix and are prone to migration, posing a risk of blooming during long-term use. In the melt-blending process of this application, due to polarity differences, voltage stabilizers containing polar groups and conjugated aromatic rings are more easily distributed onto the highly polar surface of modified barium titanate with a phenylsilane coating. Intermolecular forces (such as π-π interactions or hydrogen bonding) help improve the uniformity of voltage stabilizer dispersion within the material, reducing its excessive precipitation during long-term operation and thus maintaining a better electric field regulation effect.
[0011] Furthermore, perfluoropolyethers possess extremely low surface energy and high electronegativity. During melt blending, they can improve the wetting state of interfacial regions and assist in charge regulation of interfacial regions within the material. The synergy between modified barium titanate, voltage stabilizers, and perfluoropolyethers helps reduce the adverse effects of interfacial defects and charge accumulation on insulation performance, thereby improving the material's DC breakdown performance and electrical treeing tolerance.
[0012] In some embodiments, the method for preparing the modified barium titanate micropowder includes the following steps: S1: A modified solution is obtained by stirring a phenylsilane coupling agent and a hydroxyl-terminated polyether under acidic conditions; S2: The modified liquid is atomized and sprayed onto the surface of barium titanate to obtain modified barium titanate powder.
[0013] In some of the above embodiments, the two modifiers are uniformly dispersed through two steps: liquid phase mixing (S1) and surface spraying (S2). Subsequently, in the surface bonding reaction, silane dominates the interface anchoring, and hydroxyl-terminated polyethers are in situ composited, thereby constructing a composite interface layer with both stable and flexible buffering functions on the barium titanate surface.
[0014] In some embodiments, step S1 includes: Mix 50-70 parts of ethanol with 8-12 parts of water, add glacial acetic acid to adjust the pH to 4-5, add 3-5 parts of phenylsilane coupling agent, stir and hydrolyze at 25℃-35℃ for 30-40 minutes until the solution is clear; then add 1-2 parts of terminal hydroxyl polyether and continue stirring for 10-15 minutes to obtain the modified solution. In some of the above embodiments, in S1, the phenylsilane coupling agent hydrolyzes in a weakly acidic system to generate an active intermediate containing silanol groups. The subsequently added hydroxyl-terminated polyether, whose ether bonds and terminal hydroxyl groups on its molecular chain can form intermolecular hydrogen bonds with the silanol groups in the system. This non-covalent bonding allows the two to mix uniformly in the liquid phase, forming a stable modified liquid. At this stage, the hydroxyl-terminated polyether and the silane hydrolysis product mainly rely on physical interactions to bind, which avoids consuming the active silanol groups used for subsequent interfacial coupling and ensures that, during the subsequent spraying and coating process, the polyether molecules can be deposited simultaneously with the silane onto the surface of the barium titanate powder.
[0015] In some implementations, step S2 includes: 100 parts of barium titanate powder were added to a high-speed mixer and preheated to 45℃~55℃. At a speed of 1800~2200rpm, the modified liquid was atomized and sprayed onto the powder surface at a flow rate of 5~10 mL / min using a spray gun. After spraying, stirring was continued for 15~20 minutes. The system pressure was then reduced to -0.08~-0.095MPa, and the temperature was increased to 110℃~120℃ at a rate of 2℃ / min~4℃ / min. The mixture was then stirred at a constant temperature for 1~2 hours. After cooling, the mixture was vibrated and sieved to obtain modified barium titanate micro powder.
[0016] In some of the above embodiments, in step S2, the modified liquid is atomized and sprayed onto the surface of preheated barium titanate powder, and stirred at high speed to ensure uniform coating. Subsequently, a vacuum is drawn and the temperature is raised to 110–120°C. Vacuum removal of small molecule byproducts promotes a condensation reaction between silanes and the barium titanate surface, forming strong Si-O-Ti covalent bonds. Simultaneously, cross-linking between silanes constructs a rigid network. The hydroxyl-terminated polyether, through physical entanglement and intermolecular hydrogen bonding, tightly binds to the siloxane structure, forming a flexible interface layer. This provides excellent mechanical buffering and improves compatibility between the modified barium titanate micropowder and the polymer matrix.
[0017] In some embodiments, the phenylsilane coupling agent includes at least one of phenyltrimethoxysilane and phenyltriethoxysilane.
[0018] In some of the above embodiments, both phenyltrimethoxysilane and phenyltriethoxysilane contain hydrolyzable alkoxy groups (methoxy or ethoxy) and rigid phenyl groups. The alkoxy groups hydrolyze to generate silanol groups, which condense with the hydroxyl groups on the surface of barium titanate to form covalent bonds, anchoring the silane to the powder surface. At the same time, crosslinking between silanes forms a rigid network. The phenyl group provides hydrophobicity and π electron cloud, enhancing the interfacial compatibility between the modified powder surface and the voltage stabilizer.
[0019] In some embodiments, the hydroxyl-terminated polyether includes at least one of polyethylene glycol and polypropylene glycol.
[0020] In some of the above embodiments, both polyethylene glycol and polypropylene glycol contain abundant ether oxygen bonds and terminal hydroxyl groups. In an acidic hydrolysis system, they form hydrogen bonds with the silanol groups of phenylsilane, driving the polyether chains to wrap around the silane oligomer to form a pre-assembled structure. During the curing process, the polyether chains are locked to the gap surface of the silane crosslinking network, forming a flexible interface buffer layer to absorb the shrinkage stress of the matrix.
[0021] In some embodiments, the average particle size of the barium titanate powder is 0.2 to 1 μm.
[0022] In some of the above embodiments, the average particle size of barium titanate is controlled within 0.2–1 μm: if the particle size is too small, it is prone to agglomeration and uneven coating; if the particle size is too large, stress concentration and poor dispersion will occur. This range ensures that the modified liquid is uniformly coated on the particle surface, the powder is stably dispersed in the polypropylene matrix, and the interfacial stress is effectively buffered, which is conducive to forming a uniform electric field modulation effect.
[0023] In some embodiments, the aromatic voltage stabilizer includes at least one of 4,4'-di-tert-butylbenzophenone and 4,4'-thiobis(6-tert-butyl-m-cresol).
[0024] In some of the above embodiments, the substances all contain conjugated aromatic rings and polar groups. It can capture high-energy electrons and dissipate energy, suppressing the initiation of electrical treeing; the tert-butyl group provides steric hindrance and enhances thermal stability; at the same time, the polar groups and aromatic rings in the molecule can form hydrogen bonds and non-covalent interactions with the modified interface, realizing the targeted anchoring of the voltage stabilizer in the micro-region of the filler interface and preventing migration and precipitation.
[0025] In some embodiments, the perfluoropolyether includes at least one of type Y, type Z, type K, or type D perfluoropolyether, wherein the number-average molecular weight of the perfluoropolyether is 1000–8000 g / mol and the kinematic viscosity at 20°C is 5–500 mmHg. 2 / s.
[0026] In some of the embodiments described above, the Y-type, Z-type, K-type, and D-type perfluoropolyethers all possess a fully fluorinated backbone and extremely high electronegativity. Molecular weight: 1000–8000; viscosity: 5–500 mmHg. 2 / s ensures that it has moderate fluidity and anti-volatility during melt processing. Perfluoropolyether has good insulation stability and can regulate charge transport and accumulation at the interface, thereby helping to suppress partial discharge and the generation and propagation of electrical trees, and improving the electrical resistance and long-term stability of the insulating material.
[0027] In some embodiments, the melt index of the isotactic polypropylene matrix is 2 to 10 g / 10 min at 230°C / 2.16 kg. Based on the above embodiments, this range ensures that the melt has moderate fluidity and shear force, which can achieve uniform dispersion of modified barium titanate and interfacial enrichment of perfluoropolyether, while ensuring that the insulating layer has sufficient mechanical strength and thermal stability.
[0028] In some embodiments, the polyolefin elastomer comprises an ethylene-octene copolymer with an octene monomer content of 20–40 wt% and a melt index of 0.5–5 g / 10 min at 190°C / 2.16 kg. Based on the above embodiments, this range ensures viscosity matching with the polypropylene matrix, enhancing toughness without compromising insulation continuity, and synergistically providing stress buffering and electric field homogenization effects with the gradient modulus interface of the modified barium titanate.
[0029] In some embodiments, the antioxidant includes antioxidant 1010 and antioxidant 168, wherein the mass ratio of antioxidant 1010 to antioxidant 168 is (1-3):1. Based on the above embodiments, the antioxidant can provide protection for the polypropylene matrix, elastomer, and polyether interface layer, extending the service life of the insulating material.
[0030] Secondly, this application provides a method for preparing a modified insulating material for shielded cables, comprising: Provide raw materials for the modified insulating material according to any one of the first aspects; The raw materials are mixed, melt-extruded, and granulated to obtain a modified insulating material.
[0031] According to this application, the raw materials described in the first aspect are mixed and then melt-extruded and granulated. During the melt blending process, the voltage stabilizer spontaneously migrates to the terminal hydroxyl polyether layer on the modified barium titanate surface due to thermodynamic repulsion and polar attraction, and is anchored through hydrogen bonds and π-π stacking; the perfluoropolyether migrates to the outside of the polyether layer in the interfacial region due to its extremely low surface energy; shear force promotes uniform dispersion and self-assembly. After cooling, the components synergistically form an integrated gradient modulus interface, requiring no additional treatment.
[0032] Compared with the prior art, the beneficial effects of this application are at least as follows: This application utilizes the synergistic modification of barium titanate with phenylsilane and hydroxyl-terminated polyether to construct a composite interface layer on its surface that combines rigid anchoring and flexible buffering. This interface not only absorbs the shrinkage stress generated by the cooling crystallization of the matrix and avoids the formation of micro-defects, but also anchors the voltage stabilizer to the filler interface through hydrogen bonds in the polyether layer and the interfacial aromatic compatibility of phenylsilane, reducing its migration and precipitation. Simultaneously, the perfluoropolyether, due to its low surface energy, migrates to the interface region, and its electronegative fluorine atoms assist in charge regulation. The synergistic effect of these three elements achieves a unified solution of filler dispersion, stress buffering, stabilizer locking, and high-energy electron capture in one step, thereby improving the material's resistance to high-voltage DC breakdown and long-term anti-electrical dendrite properties. Detailed Implementation
[0033] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0034] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0035] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0036] In this specification, unless otherwise specified, "parts" refers to "parts by weight".
[0037] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0038] Polypropylene, isotactic polypropylene, melt index is 4.3 g / 10 min at 230℃ / 2.16 kg; Ethylene-octene copolymer with an octene monomer content of 31 wt% and a melt index of 2.7 g / 10 min at 190℃ / 2.16 kg. Perfluoropolyether, type K perfluoropolyether, number average molecular weight 3000 g / mol, kinematic viscosity at 20°C 250 mmHg 2 / s.
[0039] The mass ratio of antioxidant 1010 to antioxidant 168 is 3:1; The average particle size of the barium titanate powder is 0.8 μm.
[0040] Preparation Example 1 Preparation of modified barium titanate micro powder: S1: Add 60 parts ethanol and 10 parts deionized water to a reaction vessel, and adjust the pH to 4.5 by adding glacial acetic acid dropwise while stirring. Add 4 parts phenyltrimethoxysilane (phenylsilane coupling agent), and stir and hydrolyze in a 30°C constant temperature water bath for 35 minutes until the solution changes from slightly turbid to clear and transparent. Then add 1.5 parts polyethylene glycol 400 (hydroxyl-terminated polyether), and continue stirring for 12 minutes to obtain the modified solution.
[0041] S2: 100 parts of barium titanate powder were added to a high-speed mixer equipped with a steam heating jacket and preheated to 50°C. At 2000 rpm, the modified liquid prepared in S1 was atomized and sprayed onto the surface of the barium titanate powder using a spray gun at a flow rate of 8 mL / min. After spraying, high-speed stirring was continued for 18 minutes. The vacuum pump was turned on, and the system pressure was reduced to -0.09 MPa. The system temperature was raised to 115°C at a heating rate of 3°C / min, and the mixture was stirred at a constant temperature for 1.5 hours. After the reaction was completed, heating was stopped, and the mixture was purged with nitrogen for protection and cooled to room temperature. The resulting powder was then sieved through a 300-mesh vibrating sieve to obtain modified barium titanate micropowder.
[0042] Comparative Preparation Example 1 Preparation of modified barium titanate micro powder: S1: Add 60 parts ethanol and 10 parts deionized water to a reaction vessel, and adjust the pH to 4.5 by adding glacial acetic acid dropwise while stirring. Add 4 parts phenyltrimethoxysilane (phenylsilane coupling agent), and stir and hydrolyze for 35 minutes in a 30°C constant temperature water bath until the solution changes from slightly turbid to clear and transparent. (Do not add terminal hydroxyl polyether), continue stirring for 12 minutes to obtain the modified solution.
[0043] S2: 100 parts of barium titanate powder were added to a high-speed mixer equipped with a steam heating jacket and preheated to 50°C. At 2000 rpm, the modified liquid prepared in S1 was atomized and sprayed onto the surface of the barium titanate powder using a spray gun at a flow rate of 8 mL / min. After spraying, high-speed stirring was continued for 18 minutes. The vacuum pump was turned on, and the system pressure was reduced to -0.09 MPa. The system temperature was raised to 115°C at a heating rate of 3°C / min, and the reaction was carried out under constant temperature stirring for 1.5 hours. After the reaction was completed, heating was stopped, and the mixture was purged with nitrogen for protection and cooled to room temperature. The powder was then sieved through a 300-mesh vibrating sieve to obtain barium titanate micropowder modified only with phenylsilane.
[0044] Example 1 Preparation of modified insulation materials for shielded cables: Three parts by mass of the modified barium titanate micro powder obtained in Preparation Example 1 and 0.8 parts by mass of 4,4'-di-tert-butylbenzophenone were added to a high-speed mixer and mixed at 1500 rpm for 18 minutes at room temperature to obtain a pre-assembled composite functional filler.
[0045] 100 parts by weight of isotactic polypropylene, 18 parts by weight of polyolefin elastomer, the pre-assembled composite functional filler obtained in step two, and 0.4 parts by weight of antioxidant were fed into the main feed port of a twin-screw extruder. 0.5 parts by weight of perfluoropolyether were injected through a liquid metering pump from the side feed port of the middle section of the twin-screw extruder. The temperature of each section of the extruder was set to 190°C, and the screw speed was 250 rpm. The melt blend was extruded, water-cooled, and pelletized to obtain the modified insulation material granules for shielded cables.
[0046] Example 2 Preparation of modified insulation materials for shielded cables: 100 parts by weight of isotactic polypropylene, 18 parts by weight of polyolefin elastomer, 3 parts by weight of modified barium titanate micropowder obtained in Preparation Example 1, 0.8 parts by weight of 4,4'-di-tert-butylbenzophenone, and 0.4 parts by weight of antioxidant were fed into the main feed port of a twin-screw extruder. 0.5 parts by weight of perfluoropolyether were injected into the middle section side feed port of the twin-screw extruder via a liquid metering pump. The temperature of each section of the extruder was set to 190°C, and the screw speed was 250 rpm. The melt blend was extruded, water-cooled, and pelletized to obtain the modified insulating material granules for shielded cables.
[0047] Comparative Example 1 Preparation of modified insulation materials for shielded cables: Three parts by mass of the modified barium titanate micro powder obtained in Comparative Preparation Example 1 and 0.8 parts by mass of 4,4'-di-tert-butylbenzophenone were added to a high-speed mixer and mixed at 1500 rpm for 18 minutes at room temperature to obtain a pre-assembled composite functional filler.
[0048] 100 parts by weight of isotactic polypropylene, 18 parts by weight of polyolefin elastomer, the pre-assembled composite functional filler obtained in step two, and 0.4 parts by weight of antioxidant were fed into the main feed port of a twin-screw extruder. 0.5 parts by weight of perfluoropolyether were injected through a liquid metering pump from the side feed port of the middle section of the twin-screw extruder. The temperature of each section of the extruder was set to 190°C, and the screw speed was 250 rpm. The melt blend was extruded, water-cooled, and pelletized to obtain the modified insulation material granules for shielded cables.
[0049] Comparative Example 2 Preparation of modified insulation materials for shielded cables: Three parts by mass of the modified barium titanate micro powder obtained in Preparation Example 1 and 0.8 parts by mass of 4,4'-di-tert-butylbenzophenone were added to a high-speed mixer and mixed at 1500 rpm for 18 minutes at room temperature to obtain a pre-assembled composite functional filler.
[0050] 100 parts by weight of isotactic polypropylene, 18 parts by weight of polyolefin elastomer, the obtained pre-assembled composite functional filler, and 0.4 parts by weight of antioxidant were fed into the main feed port of a twin-screw extruder. The temperature of each section of the extruder was set to 190°C, and the screw speed was 250 rpm. The melt blend was extruded, water-cooled, and pelletized to obtain the modified insulation material granules for shielded cables.
[0051] Comparative Example 3 Preparation of modified insulation materials for shielded cables: 100 parts by weight of isotactic polypropylene, 18 parts by weight of polyolefin elastomer, 3 parts by weight of the modified barium titanate micropowder obtained in Preparation Example 1, and 0.4 parts by weight of antioxidant were fed into the main feed port of a twin-screw extruder. 0.5 parts by weight of perfluoropolyether were injected through a liquid metering pump from the side feed port of the middle section of the twin-screw extruder. The temperature of each section of the extruder was set to 190°C, and the screw speed was 250 rpm. The melt blend was extruded, water-cooled, and pelletized to obtain the modified insulating material granules for shielded cables.
[0052] Test section The granules obtained from the comparative examples were dried in a vacuum oven at 80°C for 4 hours, then hot-pressed at 195°C and 15 MPa using a flat vulcanizing machine, and cut into test samples after cooling.
[0053] Electrical tree initiation voltage test: The electrical tree initiation voltage of the specimens was measured according to the method specified in GB / T 21224-2007 "Test Method for Electrical Treeing of Insulating Materials". The granules obtained from the comparative examples were hot-pressed into sheet-like specimens with dimensions of 30 mm × 30 mm × 3 mm using a flat vulcanizing machine at 195°C and 15 MPa. A tungsten needle electrode with a radius of curvature of 5 μm was inserted into the specimen, with a 2 mm distance between the needle tip and the bottom flat electrode. At room temperature, the voltage was continuously increased at a rate of 500 V / s using a 50 Hz AC voltage, and the needle tip area was observed in real time using a stereomicroscope. When an electrical tree channel with a length exceeding 30 μm was observed at the needle tip, the applied voltage value was recorded as the electrical tree initiation voltage. Ten samples were tested in each group, and the characteristic value of the Weibull distribution was taken as the test result.
[0054] Electrical tree initiation voltage test after thermal aging: The electrical tree initiation voltage of the samples after thermal aging was measured according to the method specified in GB / T 21224-2007 "Test Method for Electrical Treeing of Insulating Materials". The granules obtained from the comparative examples were hot-pressed into sheet-like samples with dimensions of 30 mm × 30 mm × 3 mm using a flat vulcanizing machine at 195°C and 15 MPa. The samples were placed in a 135°C thermal aging test chamber and aged continuously in air for 720 hours. After the aging time was reached, the samples were removed and cooled to room temperature. A tungsten needle electrode with a radius of curvature of 5 μm was inserted into the aged sample, with a distance of 2 mm between the needle tip and the bottom flat electrode. Under room temperature conditions, the voltage was continuously increased at a rate of 500 V / s using a 50 Hz AC voltage, and the needle tip area was observed in real time using a stereomicroscope. When an electrical tree channel with a length exceeding 30 μm was observed at the needle tip, the applied voltage value at this time was recorded as the electrical tree initiation voltage after thermal aging. Simultaneously calculate the retention rate of the initial voltage of electrical tree after aging = (initial voltage of electrical tree after thermal aging / initial voltage of electrical tree) × 100%.
[0055] DC breakdown field strength test: The electrical strength of the specimens was measured under DC conditions according to the method specified in GB / T 1408.2-2016 "Test Methods for Electrical Strength of Insulating Materials Part 2: Additional Requirements for Application of DC Voltage Tests". The granules obtained from the comparative examples were hot-pressed at 195℃ and 15 MPa using a flat vulcanizing machine to prepare thin film specimens with a thickness of 0.2 mm. A unequal-diameter brass ball-plate electrode system with a diameter of 25 mm was used. The specimens were placed between the electrodes and immersed entirely in room temperature silicone oil to prevent surface flashover. A DC voltage was applied at a boost rate of 2 kV / s until the specimen broke down. The voltage value at the moment of breakdown was recorded and divided by the measured thickness of the specimen at the breakdown point to calculate the DC breakdown field strength (kV / mm). Fifteen samples were tested in each group, and the characteristic value of the Weibull distribution was taken as the test result.
[0056] The test results are shown in Table 1 below. Table 1
[0057] According to Table 1, Example 1 exhibits higher DC breakdown field strength, higher DC treeing initiation voltage, and better treeing initiation voltage retention rate after thermal aging compared to Comparative Examples 1-3. This indicates that the modified insulation material provided in this application is more suitable for shielded cable insulation applications that require comprehensive resistance to high-voltage DC breakdown and long-term anti-treeing properties. The possible reason is that in Comparative Example 1, since the barium titanate micropowder was only modified by a phenylsilane coupling agent without the introduction of terminal hydroxyl polyethers for synergistic modification, the filler surface only had a rigid phenylsilane anchoring layer, lacking the flexible buffer network constructed by the terminal hydroxyl polyethers. On the one hand, due to the abrupt change in modulus between the rigid barium titanate and the flexible polypropylene matrix, the interfacial thermal shrinkage stress cannot be effectively released during the cooling crystallization process, easily inducing microscopic interfacial defects. On the other hand, the voltage stabilizer can only bind to the phenylsilane singly through π-π interactions, lacking the high-density hydrogen bonding and topological confinement effects provided by the polyether network, resulting in insufficient anchoring strength on the filler surface. The increase in microscopic defects and the decrease in stabilizer enrichment: In Comparative Example 2, although the modified barium titanate micropowder was prepared, the lack of charge regulation at the system interface due to the absence of perfluoropolyether resulted in the absence of charge regulation at the system interface. Under these conditions, the high-energy electrons injected into the system could not be effectively captured when the insulating material was subjected to the dual stress of long-term high-voltage DC and thermal aging. These high-energy electrons affected the polymer molecular chains and organic interface layer, not only accelerating the degradation of the insulating matrix but also destroying the anchoring structure of the voltage stabilizer at the interface. This caused the chemical dissipation function of the voltage stabilizer to rapidly decay with the extension of aging time. Therefore, although the initial DC treeing voltage of Comparative Example 2 was close to that of Example 1, it experienced a precipitous drop after thermal aging, and the retention rate was significantly lower than that of Example 1. In Comparative Example 3, although the modified barium titanate micropowder was prepared and perfluoropolyether was added, the absence of aromatic voltage stabilizers in the formulation resulted in the lack of chemical energy dissipation functional components. When high-energy electrons are injected into the insulating layer, although the fluorine atoms of the perfluoropolyether can partially capture and restrict electron migration, the lack of voltage stabilizers for active absorption of electron energy and efficient quenching of the conjugated structure means that some of the trapped electrons will still release energy, triggering free radical degradation reactions of the polypropylene macromolecular chains. Furthermore, during long-term thermal aging, the lack of stabilizers for capturing and eliminating free radicals leads to the continuous accumulation of degradation and damage to the interface by high-energy electrons, resulting in a decrease in the initiation voltage of electrical trees after thermal aging, with a retention rate of only 61.2%.
[0058] As shown in Examples 1 and 2, the stepwise premixing process has a certain impact on the DC breakdown field strength, electrical tree initiation voltage, and retention rate after aging of the material. In Example 2, although the formulation components are exactly the same as in Example 1, because the pre-assembly of the composite functional filler in step two was not carried out, and all components were put into a twin-screw extruder for blending at once, the voltage stabilizer failed to be pre-anchored to the phenylsilane layer on the surface of the modified barium titanate micropowder through π-π conjugated stacking before melt blending. Under these conditions, the voltage stabilizer molecules were largely diluted and indiscriminately dispersed by the PP melt during the high-temperature mixing process, and only a small portion could migrate to the filler surface under thermodynamic drive, resulting in a decrease in the enrichment concentration and anchoring efficiency of the voltage stabilizer around the filler, thereby affecting the overall performance of the material.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A modified insulating material for shielded cables, characterized in that, Includes the following quantities of raw materials: 100 parts by weight of isotactic polypropylene matrix, 15-20 parts by weight of polyolefin elastomer, 2-5 parts by weight of modified barium titanate micro powder, 0.5-1 parts by weight of aromatic voltage stabilizer, 0.2-1 parts by weight of perfluoropolyether, and 0.3-0.5 parts by weight of antioxidant. The modified barium titanate micro powder is obtained by treating barium titanate with a phenylsilane coupling agent and a terminal hydroxyl polyether.
2. The modified insulating material according to claim 1, characterized in that, The preparation method of the modified barium titanate micro powder includes the following steps: S1: A modified solution is obtained by stirring a phenylsilane coupling agent and a hydroxyl-terminated polyether under acidic conditions; S2: The modified liquid is atomized and sprayed onto the surface of barium titanate to obtain modified barium titanate powder.
3. The modified insulating material according to claim 2, characterized in that, Step S1 includes: Mix 50-70 parts of ethanol with 8-12 parts of water, add glacial acetic acid to adjust the pH to 4-5, add 3-5 parts of phenylsilane coupling agent, and stir at 25℃-35℃ for 30-40 minutes until the solution is clear; then add 1-2 parts of terminal hydroxyl polyether and continue stirring for 10-15 minutes to obtain the modified solution.
4. The modified insulating material according to claim 2, characterized in that, Step S2 includes: 100 parts of barium titanate powder were added to a high-speed mixer and preheated to 45℃~55℃. At a speed of 1800~2200rpm, the modified liquid was atomized and sprayed onto the powder surface using a spray gun at a flow rate of 5~10 mL / min. After spraying, stirring was continued for 15~20 minutes. The system pressure was then reduced to -0.08~-0.095MPa, and the temperature was increased to 110℃~120℃ at a rate of 2℃ / min~4℃ / min. The mixture was then stirred at a constant temperature for 1~2 hours. After cooling, the mixture was vibrated and sieved to obtain modified barium titanate micro powder.
5. The modified insulating material according to claim 2, characterized in that, The modified barium titanate micro powder satisfies at least one of the following conditions: 1) The phenylsilane coupling agent includes at least one of phenyltrimethoxysilane and phenyltriethoxysilane; 2) The hydroxyl-terminated polyether includes at least one of polyethylene glycol and polypropylene glycol; 3) The average particle size of the barium titanate powder is 0.2 to 1 μm.
6. The modified insulating material according to claim 1, characterized in that, The aromatic voltage stabilizer includes at least one of 4,4'-di-tert-butylbenzophenone and 4,4'-thiobis(6-tert-butyl-m-cresol).
7. The modified insulating material according to claim 1, characterized in that, The perfluoropolyether includes at least one of Y-type, Z-type, K-type, or D-type perfluoropolyether, wherein the number-average molecular weight of the perfluoropolyether is 1000–8000 g / mol, and the kinematic viscosity at 20°C is 5–500 mmHg. 2 / s.
8. The modified insulating material according to any one of claims 1 to 7, characterized in that, The raw materials meet at least one of the following conditions: 1) The melt index of the isotactic polypropylene matrix is 2–10 g / 10 min at 230℃ / 2.16 kg; 2) The polyolefin elastomer includes an ethylene-octene copolymer, with an octene monomer content of 20-40 wt% and a melt index of 0.5-5 g / 10 min at 190℃ / 2.16 kg. 3) The antioxidants include antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is (1~3):
1.
9. A method for preparing a modified insulating material for shielded cables, characterized in that, include: Provide raw materials for the modified insulating material according to any one of claims 1 to 8; The raw materials are mixed, melt-extruded, and granulated to obtain a modified insulating material.
